Impact of Om Mantra Chanting in Human Life: An Analysis from a Sociological Perspective (Prithvi Academic Journal, 2026)
The term “Om” has been used as a chant in the Sanatan tradition as a beneficial Mantra for maintaining a sound mind in a sound body. This word has been in use extensively in meditation and Yoga. This research aimed to delve into the profound importance of ‘Om’ and the effects of chanting this Mantra on individual well-being, encompassing socio-cultural, physical and psycho-social dimensions. To achieve the objective, both primary and secondary data were used under a qualitative research design. Primary data were collected through the case study method. Twenty-three case studies were conducted using purposive and snow ball sampling techniques. The secondary data were collected from previous research reports, articles and references. Both types of data were analyzed using content analysis. “Om”chanting meditation has been found to be effective, meaningful, useful, and essential for a healthy body and mind of an individual from various perspectives. Multiple benefits of ‘Om’ chanting emerged as thematic categories through the analysis of different cases and the respondents. These benefits include control of the blood pressure, reduction of depression, anxiety and stress, physiological relaxation, psychological well-being.